PACKED LUNCH PHENOMENON FOR HUSBAND: NETIZENS' CONTESTATION ABOUT GENDER ROLES - Tya Asih Dayu Purwitasari; Muhammad Rizqy Al-Mubarok (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
Packed lunch for husbands was a viral thread on Twitter in 2020. The thread containing photos of food and the recipe went viral because of the many responses from netizens regarding packed lunch for husbands related to gender roles. This article questions how gender roles relate to packed lunch for husbands, which netizens disputed in this thread. This research uses descriptive analysis method. By collecting primary data in the form of phrases, words, sentences contained in the @rainydecember thread along with citizen comments. After the data was collected, it was analyzed using Betty Friedan's feminine mystique perspective, then described. The results showed that the owner of the thread was shackled to the mystical feminine who consciously or not helped to spread and perpetuate it by making packed lunch for her husband. The thread then received mixed responses, netizens who widely supported the thread indicated that they were constructed of a patriarchal ideology and considered the ideal woman who was good at taking care of the household as a mystical feminine. As for those who are against these threads, they have the potential to misogyny and build stereotypes on women, especially aimed at the thread owner